Effects of different topical anesthetics on pain from needle insertion and injection, and the influence of anxiety in patients awaiting endodontic treatment - Fatih Aksoy; Samet Tosun (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to evaluate the effects of 5% lidocaine and 2.5% lidocaine/2.5% prilocaine topical anesthetic on pain during needle insertion and infiltration injection in the labial mucosa of anterior maxillary teeth, and to assess the relationship between patients’ anxiety and pain scores.Materials and MethodsThe Modified Dental Anxiety Scale questionnaire was applied and recorded. Patients were randomly divided into 4 groups (n = 30), as follows: G1 group: 5% lidocaine and placebo for 1 minute, G2 group: 2.5% lidocaine/2.5% prilocaine and placebo for 1 minute, G3 group: 5% lidocaine and placebo for 3 minutes, and G4 group: 2.5% lidocaine/2.5% prilocaine and placebo for 3 minutes. Before the application of topical anesthesia, one side was randomly selected as the topical anesthesia and the contralateral side as the placebo. The pain levels were measured with Visual Analog Scale (VAS) immediately after needle insertion and injection and were compared. The correlation between anxiety and pain scores was analyzed.ResultsAdministration of 5% lidocaine for 1 minute had significantly higher pain scores for both insertion and infiltration injection than the other groups (p < 0.05). There was a significant moderate positive correlation between dental anxiety and the injection-induced VAS pain score in the placebo side in all groups (p < 0.05).ConclusionsTopical anesthetics significantly reduced the pain caused by both needle insertion and injection pain in comparison to the placebo side. The pain scores of patients with dental anxiety were lower on the topical anesthesia compared to the placebo side.Trial RegistrationThai Clinical Trials Registry Identifier: TCTR20201217002